KONTRIBUSI MINAT BELAJAR DAN E-LEARNING SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS X JURUSAN TEKNIK KOMPUTER DAN JARINGAN SMK NEGERI 1 AIR PUTIH KABUPATEN BATUBARA SUMATERA UTARA - Faridah Hanum; Legiman Slamet; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The background of this research based on the result of the Network Basic training subject wasnot optimal on semester 2013/2014, of which 30.56% scored below the minimum complete ness criteria (KKM).This research is acorrelational study description.The purpose of this research was to reveal how much the contribution of learning and e-learning as Media learning jointly and severally on learning outcomes. The study population numbered 72 people and the sample amounted to 42 students of class X TKJ SMKN 1 Air Putih. The sampling technique was randomly (Simple Random Sampling). Data student learning out comes obtained from X TKJ home room. While data on learning and e-learning as media learning was collected through question naires distributed to students by using a Likert scale that has been tested for validity and reliability. The result showed that (1) interest in learning and e-learning as media learning together contribute significantly to the results of class X student Department of TKJ SMK N 1 Air Putih by 35.30%, (2) interest in learning contribute significantly to the results of class X student Department of TKJ SMK N Air Putih by 22.28%, (3) e-learning as media learning contribute significantly to the results of class X student Department of TKJ SMK N 1 Air Putih by 30.14% , So it can be concluded that the interest in learning and e-learning as media learning  contribute to the results of class X student in the Department of TKJ SMK N 1 Air Putih, ncreasing interest in higher learning and the use of e-learning as media learning , the higher the learning outcomes. Key-word : Interest in Learning, E-learning As Media Learning, Learning Outcomes.